Re-Wired/Re-Mixed: Event for Dismembered Body, Performance and interactive installation, Exhibited at: Radical Ecologies, Perth Institute of Contemporary Art, Perth, 3-7 August, 2016 - Stelarc, Stelarc (2017)
We increasingly operate remotely online and across different time zones. This performance explores the sensory experience of a body fragmented and distributed physically, online and across time. The artist wore a head-up display, sound cancelling earphones and a robotic, exoskeleton arm, causing the body to see through the eyes of someone in London, hear through the ears of someone in New York, while anyone, anywhere could access and choreograph his right arm. What constitutes embodiment, agency and identity become problematic.